2014
DOI: 10.1186/1472-6882-14-261
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss herbal intervention therapy (W-LHIT) a non-appetite suppressing natural product controls weight and lowers cholesterol and glucose levels in a murine model

Abstract: BackgroundThe prevalence of obesity is increasing in industrialized countries. Obesity increases the risk of coronary artery disease, stroke, cancer, hypertension, and type-2 diabetes. Unfortunately, conventional obesity drug treatment is often associated with adverse effects. The objective of this study was to evaluate a novel natural formula, Weight loss herbal intervention therapy (W-LHIT), developed from traditional Chinese medicine, for weight control in a high-fat-diet (HFD) induced obesity murine model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Moon et al [39] showed that anti-obesity effects of quercetin-rich onion peel extract were followed by up-regulation of fatty acid binding protein 4 (Fabp4) in high fat-fed rats. Yang et al [40] demonstrated that weight loss herbal intervention therapy (W-LHIT) reduced body weight, without suppression of appetite, in obese mice, by significantly increasing the gene expression of Pparg (peroxisome proliferator activated receptor gamma) and Fabp4 (fatty acid binding protein 4) epdidymal fat tissues. In contrast, Lee et al [41] Monascus pilosus-fermented black soybean inhibits lipid accumulation in adipocytes and in high-fat diet-induced obese mice, but significantly lower gene expression of adipogenesis-related genes like peroxisome proliferator-activated receptor gamma (Pparg) and fatty acid-binding protein 4 (Fabp4).…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al [39] showed that anti-obesity effects of quercetin-rich onion peel extract were followed by up-regulation of fatty acid binding protein 4 (Fabp4) in high fat-fed rats. Yang et al [40] demonstrated that weight loss herbal intervention therapy (W-LHIT) reduced body weight, without suppression of appetite, in obese mice, by significantly increasing the gene expression of Pparg (peroxisome proliferator activated receptor gamma) and Fabp4 (fatty acid binding protein 4) epdidymal fat tissues. In contrast, Lee et al [41] Monascus pilosus-fermented black soybean inhibits lipid accumulation in adipocytes and in high-fat diet-induced obese mice, but significantly lower gene expression of adipogenesis-related genes like peroxisome proliferator-activated receptor gamma (Pparg) and fatty acid-binding protein 4 (Fabp4).…”
Section: Discussionmentioning
confidence: 99%
“…8‐week‐old female Kunming mice purchased from the Shandong Laboratory Animal Center (Pengyue, Jinan, China). Safety testing experiments were performed according to the methods reported in previous study 30 . And the studies were approved by the Animal Care and Use Committee (Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…Safety testing experiments were performed according to the methods reported in previous study. 30 And the studies were approved by the Animal Care and Use Committee (Approval No. DWLL201804305) of Henan University of Chinese Medicine and were performed in strict accordance with the NIH guidelines for the care and use of laboratory animals.…”
Section: Safety Testingmentioning
confidence: 99%
“…Weight loss herbal intervention therapy (W-LHIT) is a Chinese medicine (CM) prescription, consisting of 5 Chinese herbal medicines: Ganoderma lucidum , Coptis chinensis , Astragalus membranaceus , Nelumbo nucifera gaertn and Fructus aurantii. In our previous studies, we have showed that W-LHIT significantly and safely reduced the body weight of mice with high-fat diet, and normalized their glucose and cholesterol levels, without suppressing appetite ( 9 ). In addition, in our phase I clinical study with 14 patients with simple obesity, the W-LHIT capsules demonstrated clinically significant weight loss (Cao et al.…”
Section: Introductionmentioning
confidence: 99%